INVISIBLE BARRIERS OF CLASS IN EMMA MOVIE BY AUTUMN DE WILDE - Fitriya Nur Azizah; Dewi Candraningrum (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
Social class remains a central theme in literature and film, reflecting persistent inequalities in human relations. While most studies on Jane Austen’s Emma (2020) emphasize adaptation, gender, or historical settings, limited research has explored how class hierarchy operates ideologically in Autumn de Wilde’s 2020 film adaptation. Addressing this gap, the present study examines the invisible barriers of class in Emma (2020) through a Marxist framework. Using a qualitative descriptive approach, ten selected scenes were analyzed to reveal how clothing, marriage arrangements, and social interactions construct class distinctions. The findings indicate that Emma Woodhouse, representing the bourgeoisie, exercises ideological and cultural authority over Harriet Smith’s decisions, while Harriet’s compliance exemplifies lower-class subordination. Visual markers such as costumes and rituals like dances further reinforce symbolic hierarchies that sustain inequality. This study contributes a novel perspective by integrating Marxist theory with visual and narrative analysis to uncover how cultural and symbolic capital perpetuate class domination. The results highlight the film’s critical value for cultural and film studies, offering insights into how class ideology continues to shape representations of power and privilege in modern adaptations of classic works.